The Paradox of Shape: On the Representation of Women in the Sixteenth Century - Michelacci, Lara (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2023)
In the third part of his Dialogus de viris et foeminis aetate nostra florentibus, Paolo Giovio lists over one hundred illustrious women of his time and paints an unusual picture of Italian society. The catalogue is not a review of the virtues or superiority of women but rather an account of the political use of female representations. Women are associated with the political status of a city, and all references to the physicality of women illustrate the paradox of politics itself. The female body is used as a test case to examine the exercise of power and to demonstrate the reasons for different political strategies in different courts before the dramatic Sack of Rome in 1527. Through an analysis of the Dialogus and comparison with other contemporary treatises on female figures, this article highlights the political use of the female shape, described and paradoxically modified, according to government strategy. A salient example is the ambiguous representation of Vittoria Colonna, seen by Paolo Giovio as the model for women in the Renaissance.